A comparative study of the contents and methods of teaching social studies in secondary schools in the Philippines and Thailand - Deetae, Monthien 1942- ([Quezon City s.n.], 1974)
This is a comparison of the contents and methods of teaching secondary social studies in Thailand and in the Philippines through documentary analysis. The primary purpose of this study is to find the extent of variations in contents relative to organizations and sequences as well as approaches in teaching the different disciplines. The findings revealed that Thai students are moralistic since they are dominantly Buddhist in orientation.
Thesis (M.A.T.Social Studies)--University of the Philippines.
Keywords: Social sciences -- Study and teaching (Secondary).